Facile and scalable preparation of highly wear-resistance superhydrophobic surface on wood substrates using silica nanoparticles modified by VTES - Jia, Shanshan; Liu, Ming; Wu, Yiqiang; Luo, Sha; Qing, Yan; Chen, Haibo (Applied surface science, 2016)
Highly wear-resistance superhydrophobic surface on wood substrates was fabricated using silica nanoparticles modified by VTES. [Display omitted] •Superhydrophobic surface on wood substrates was efficiently fabricated using nanoparticles modified by VTES.•The superhydrophobic surface exhibited a CA of 154° and a SAclose to 0°.•The superhydrophobic surface showed a durable and robust wear-resistance performance. In this study, an efficient, facile method has been developed for fabricating superhydrophobic surfaces on wood substrates using silica nanoparticles modified by VTES. The as-prepared superhydrophobic wood surface had a water contact angle of 154° and water slide angle close to 0°. Simultaneously, this superhydrophobic wood showed highly durable and robust wear resistance when having undergone a long period of sandpaper abrasion or being scratched by a knife. Even under extreme conditions of boiling water, the superhydrophobicity of the as-prepared wood composite was preserved. Characterizations by scanning electron microscopy, energy-dispersive X-ray spectroscopy, and Fourier transform infrared spectroscopy showed that a typical and tough hierarchical micro/nanostructure was created on the wood substrate and vinyltriethoxysilane contributed to preventing the agglomeration of silica nanoparticles and serving as low-surface-free-energy substances. This superhydrophobic wood was easy to fabricate, mechanically resistant and exhibited long-term stability. Therefore, it is considered to be of significant importance in the industrial production of functional wood, especially for outdoor applications.